The transgender studies reader - Stryker, Susan; Whittle, Stephen (Routledge, 2006)
Although the term "transgender" itself has achieved familiarity only within the past decade, this authoritative collection of articles demonstrates that the study of behaviors, bodies, and subjective identities which contest common Eurocentric notions of gender has a history stretching back at least to the early 20th century. Transgender studies is the latest area of academic inquiry to grow out of the exciting nexus of queer theory, feminist studies, and the history of sexuality. Because transpeople challenge our most fundamental assumptions about the relationship between bodies, desire, and identity, the field is both fascinating and contentious. The Transgender Studies Reader puts between two covers fifty influential texts with new introductions by the editors that, taken together, document the evolution of transgender studies in the English-speaking world. By bringing together the voices and experience of transgender individuals, doctors, psychologists, and academically-based theorists, this volume will be a foundational text for the transgender community, transgender studies, and related queer theory.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; interdisciplinarité; occident; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques

Queering the Binaries: Transsituated Identities, Bodies, and Sexualities - Cromwell, Jason (The transgender studies reader, 2006)
Keywords: 1900-1999; approches et analyses; corps; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques; états-unis